Dialogic culture as a component of the teaching competence of future teachers in primary schools (Pedagogy of Higher and Secondary Education, 2012)
Dovbenko S. Dialogic culture as a component of the teaching competence of future teachers in primary schools.In article problems of formation of dialogical culture as compound pedagogical competence of future teachers of elementary school are considered. Pedagogical competence should provide appropriate vocational training of the graduate in the conditions of the higher school his competitive capacity in the market of educational services.
Keywords: dialogical culture; professional competence